Investigations of Dynamic Behaviors of Face Gear Drives Associated with Pinion Dedendum Fatigue Cracks - Zhengminqing Li; Shuang Liu; Rupeng Zhu; Xiaodong Xu (Shock and Vibration)
Face gear dynamics is addressed by many scholars. However, dynamic behaviors of face gear drives associated with pinion dedendum fatigue cracks are yet to be investigated. Thus, in the study, a calculation solution of static transmission errors (STE) of face gear drives associated with pinion dedendum fatigue cracks is constructed, based on the proposed equivalent face gear drives, and a four-degree-of-freedom (DOF) dynamic model of face gear drives is formulated. The dynamic behaviors of an example case of face gear drives associated with pinion dedendum fatigue cracks are investigated. The simulation results indicate natural frequencies of face gear drives would be decreased with pinion dedendum fatigue crack extensions; the relationship between accelerations and velocities of face gear drives, dynamic mesh forces, and vibration accelerations at bearings would also be changed. However, pinion dedendum fatigue cracks of face gear drives are detected difficultly, due to simulation result similarities. Therefore, a determination solution for pinion dedendum fatigue cracks of face gear drives is proposed. The result shows a trend of vibration accelerations at bearings, namely, a first decreasing and then increasing tendency, which could be beneficial to detecting pinion dedendum fatigue cracks of face gear drives. These contributions would improve engineering applications of face gear drives in the future.